2017
DOI: 10.1016/j.ejor.2017.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Is there a prison size dilemma? An empirical analysis of output-specific economies of scale

Abstract: We advocate a nonparametric multi-output framework to estimate outputspecific economies of scale and we apply this model to male prisons in England and Wales over the sample period 2009-2012. To estimate output-specific returns to scale in prisons, we consider not only the cost-per-place, but also qualitative outputs such as purposeful out-of-cell activity and successful reintegration. Furthermore, we introduce environmental heterogeneity using the characteristics of the prison(ers). England and Wales offers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Given the role of economic cycles, internationalisation is used to offset the performance of some countries with that of others, thereby turning disadvantages into advantages. The prospect of accessing more affordable factors of production in other countries means that companies view internationalisation as a means of achieving cost reductions and economies of scale (Cuervo-Cazurra and Genc, 2008;Lockyer, 2013;Hennebel et al, 2017).…”
Section: Market Characteristics -Choice Of Strategymentioning
confidence: 99%
“…Given the role of economic cycles, internationalisation is used to offset the performance of some countries with that of others, thereby turning disadvantages into advantages. The prospect of accessing more affordable factors of production in other countries means that companies view internationalisation as a means of achieving cost reductions and economies of scale (Cuervo-Cazurra and Genc, 2008;Lockyer, 2013;Hennebel et al, 2017).…”
Section: Market Characteristics -Choice Of Strategymentioning
confidence: 99%
“…The research is based on modern developments in the field of criminology (Koryakin, 2017), economics (Devine-Wright, Baybutt, & Meek, 2019), management (Hennebel, Simper, & Verschelde, 2017), technology of penitentiary production (Death & Horan, 2018) and organization of convicts' labor (Simioni, 2019). The work took into account the experience of organizing food self-sufficiency in penitentiary institutions (Bejarano-Roncancio, Celedón-Dangond, & Socha-Gracia, 2015), as well as the possibility of creating new types of correctional institutions (Gilmer & Comerford, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Estimated cost and arrest data for criminals between 2001-2012, the mean cost equations of urban and rural police stations, together with demographic, economic, and social factors, it was found that urban police stations were economies of scale, but local police stations did not result in economies of scale. Hennebel, Simperet, and Verschelde [8] analyzed the scale of prisons in England and Wales, finding economies of scale of prisons should have a capacity of 554-1,187 people, with an annual cost of around £23-37 million per site. However, the researcher recommended that prisons focus on quality improvement and environmental management as prisons had a large number of inmates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the law and international principle, Thailand Juvenile Vocational Training Center (JVTC), Department of Juvenile Observation and Protection (DJOP), Ministry of Justice, also must address treatment needs, develop skills, and rehabilitate juveniles that the court has ordered probation to protect the welfare and to improve the quality of life. Juvenile offenders were characterized by a high risk of recidivism, povertystricken, and low investment in potential development, so they were often unsuccessful in life and got set back because they were not well educated [12] and were not interested in studying, and often had to drop out of school [8]. Carter [2] explained that childhood laborers with a history of violent behavior and a previous offense were less successful in their lives than the youth without a history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation